Williams on external reasons - Viney, Marcus Wayne, author; Tropman, Beth, advisor; Rhodes, Matthew, committee member; Losonsky, Michael, committee member (Colorado State University. Libraries, 2010)
Bernard Williams has argued for the controversial thesis that there are no external reasons for action. External reasons are desire-independent reasons for action, i.e. reasons whose existence does not depend on the desires of an agent. The thrust of Williams' argument is that an agent's reasons for action must always depend on his or her desires. The overall purpose of this thesis is to clarify and critically examine Williams' argument against external reasons. In chapter 1 I formalize and explain Williams' argument step-by-step. In addition to this I confront one prominent objection to the argument's validity, which alleges that it contains an equivocation on the term "reason." I argue that this objection fails and that Williams' argument is valid. In chapter 2 I turn to the soundness of Williams' argument and examine the truth of the premises one by one. In doing this I attempt to uncover important assumptions that underlie Williams' reasoning. I confront several objections to the premises, but I argue that none of them succeed in blocking Williams' conclusion. In the final chapter I consider the wider issues facing Williams' argument. First I confront three objections which allege that Williams' conclusion has certain unacceptable consequences. I draw from Williams' work to exonerate his argument on all three counts. Second I discuss two ways the critic might grant the soundness of Williams' argument, but neutralize the impact of his conclusion. While I defend Williams' argument on nearly every point, my primary aim is not to offer a definitive case for the argument. Rather my aim is simply to show that Williams' argument is stronger than some critics might suppose and that it is worthy of further consideration.
Covers not scanned.
Keywords: Act (Philosophy)